(untitled) (The Strategic Review for Southern Africa, 2020)
In Pursuit of Freedom and Justice: A Memoir by veteran nationalist Cephas Msipa joins the list of memoirs and biographies of women and men who fought for majority rule in Zimbabwe. Born on 7 July 1931 in the Shabani District in the Midlands province (p 1), "a teacher by profession and a politician by circumstances" (p ix), Msipa was a key member of the nationalist movement and a prominent politician in the post-colonial era. Born of poor peasants, Msipa's childhood was typical of many of his generation until he became politicised at a young age, especially during encounters with Benjamin Burombo, a proto-nationalist and a friend of his father, whom he describes as his political mentor (p 4).